Indigenous Mathematics of Native North Americans. - DeCesare, Rich (2007)
Keywords: dept.mat; faculty_collection; sabbatical_report

Born This Day: A Book of Birthdays and Quotations of Prominent People Through the Centuries - Nowlan, Robert A. (McFarland & Co., 2007)
"For each date, a diverse dozen speakers were chosen based on prominence; the quality of the quotation; the uniqueness of the speaker with relation to gender, time period, nationality and vocation; and conflicting social, political, religious or philosophical background. Includes a quotation from each person that allows a glimpse of their personality"--Provided by publisher.
Keywords: Quotations, English; Birthday books; Literary calendars; dept.mat; faculty_collection

On the fewest nets problem for convex polyhedra - Pinciu, Val (2007)
Given a convex polyhedron with n vertices and F faces, what is the fewest number of pieces, each of which unfolds to a simple polygon, into which it may be cut by slices along edges? Shephard's conjecture says that this number is always 1, but it's still open. The fewest nets problem asks to provide upper bounds for the number of pieces in terms of n and/or F. We improve the previous best known bound of F/2 by proving that every convex polyhedron can be unfolded into no more than 3F/8 non-overlapping nets. If the polyhedron is triangulated, the upper bound we obtain is 4F/11.
Keywords: Computational geometry; Convex polyhedrons; Simple polygon; Upper Bound; dept.mat; ⛔ No DOI found